Case Report: JAK inhibitors for the treatment of anti-melanoma differentiation-associated gene 5-positive dermatomyositis with spontaneous pneumomediastinum - Yang, Xin; Cui, Xiaoguang; Li, Xueyi (Frontiers in Medicine, 2025)
BackgroundSpontaneous pneumomediastinum (SPNM) occurred more frequently in dermatomyositis (DM) patients with anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody than in DM patients without anti-MDA5 antibody. SPNM has been indicated as a risk factor for death in anti-MDA5-positive DM. There have been no clinical studies evaluating the treatment strategy for SPNM in anti-MDA5-positive DM.MethodsWe present a series of five cases in which the administration of Janus kinase (JAK) inhibitors improved the clinical condition of anti-MDA5-positive DM patients with SPNM.ResultsClinical conditions of the four patients who were given JAK inhibitors after the diagnosis of SPNM were all improved. SPNM symptoms of the patient who was not commenced on JAK inhibitors progressed, and the patient died of severe pulmonary infection.ConclusionJAK inhibitors appear to be an efficient therapeutic option in the treatment of anti-MDA5-positive DM with SPNM.